2022
DOI: 10.48550/arxiv.2205.12774
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

$4$-manifolds with boundary and fundamental group $\mathbb{Z}$

Abstract: We classify topological 4-manifolds with boundary and fundamental group Z, under some assumptions on the boundary. We apply this to classify surfaces in simply-connected 4manifolds with S 3 boundary, where the fundamental group of the surface complement is Z. We then compare these homeomorphism classifications with the smooth setting. For manifolds, we show that every Hermitian form over Z[t ±1 ] arises as the equivariant intersection form of a pair of exotic smooth 4-manifolds with boundary and fundamental gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…For smooth knottings of surfaces in the 4-ball the reader is directed towards Hayden [24], Hayden-S. Kim-Miller-Park-Sundberg [25] Hayden-Kjuchukova-Krishna-Miller-Powell-Sunukjian [26], Juhász-Miller-Zemke [23] and Oba [33]. Conway-Piccirillo-Powell [11] showed that every 2-handlebody with a 3-sphere boundary contains a pair of smoothly knotted disks [11].…”
Section: Introductionmentioning
confidence: 99%
“…For smooth knottings of surfaces in the 4-ball the reader is directed towards Hayden [24], Hayden-S. Kim-Miller-Park-Sundberg [25] Hayden-Kjuchukova-Krishna-Miller-Powell-Sunukjian [26], Juhász-Miller-Zemke [23] and Oba [33]. Conway-Piccirillo-Powell [11] showed that every 2-handlebody with a 3-sphere boundary contains a pair of smoothly knotted disks [11].…”
Section: Introductionmentioning
confidence: 99%